Milk fermentation by monocultures or co-cultures of Streptococcus thermophilus strains - Han, Mei; Wu, Yanfeng; Guo, Xiaojuan; Jiang, Lili; Wang, Xin; Gai, Zhonghui (Frontiers in Bioengineering and Biotechnology, 2022)
Direct vat-set starter cultures are the key ingredient for the production of fermented dairy products. The characteristics of the strains used for fermentation determine the fermentation time and the texture and flavor of the fermented milk products. In this study, a large-scale analysis of the phenotypic characteristics of Streptococcus thermophilus strains was conducted. All 100 S. thermophilus strains were divided into six groups according to the acid production rate and into two groups according to the extracellular polysaccharide-producing ability. In addition, the abilities of all of the strains to ferment different carbon sources were investigated. A universal medium, in which different carbon sources were optimized (0.5% lactose and 3.5% glucose), was prepared to culture all of the test strains. Fermentation by 40 strains was tested under pH-controlled conditions using this universal culture medium. After 5–7 h of fermentation, the optical density (OD) values of all fermented products exceeded 10, suggesting the potential for high-density cultivation of S. thermophilus. Although the OD could be further increased by adding more glucose, this may have hindered subsequent lyophilization because of high residual lactic acid in the fermented product. Next, the growth characteristics of different S. thermophilus strains in co-cultures were evaluated and compared. The results revealed the existence of symbiotic or competitive relationships between different S. thermophilus strains. Based on the findings, the mixing ratio of three symbiotic S. thermophilus strains was optimized. A co-culture of these three strains yielded fermented milk with high viscosity, low post-acidification, good sensory properties, and good processability.